2012
DOI: 10.1152/jn.01009.2011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced intrinsic excitability and EPSP-spike coupling accompany enriched environment-induced facilitation of LTP in hippocampal CA1 pyramidal neurons

Abstract: Environmental enrichment (EE) is a well-established paradigm for studying naturally occurring changes in synaptic efficacy in the hippocampus that underlie experience-induced modulation of learning and memory in rodents. Earlier research on the effects of EE on hippocampal plasticity focused on long-term potentiation (LTP). Whereas many of these studies investigated changes in synaptic weight, little is known about potential contributions of neuronal excitability to EE-induced plasticity. Here, using whole-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 88 publications
(116 reference statements)
14
85
0
Order By: Relevance
“…While increased intrinsic excitability was observed after a relatively short duration of enrichment (<35 days; [35]), this was not the case in another study which used a longer duration (8 weeks; [9]). Interestingly, it has recently been pointed out in a review article, that enhanced synaptic properties and population spike induction by environmental enrichment, were mostly observed in studies with a relatively short housing duration (<4 weeks; [10]).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…While increased intrinsic excitability was observed after a relatively short duration of enrichment (<35 days; [35]), this was not the case in another study which used a longer duration (8 weeks; [9]). Interestingly, it has recently been pointed out in a review article, that enhanced synaptic properties and population spike induction by environmental enrichment, were mostly observed in studies with a relatively short housing duration (<4 weeks; [10]).…”
Section: Introductionmentioning
confidence: 76%
“…Previous studies reported both an increased [35] and a similar [9] intrinsic excitability of CA1 pyramidal cells after an exposure to an EE. To test whether the exposure of the mice to the EE increased the excitability of CA1 pyramidal cells in our experiment, we first compared the amount of current needed to trigger at least one spike (minimum current: MC), using the IV protocol (see methods; Fig.…”
Section: Environmental Enrichment Increases Intrinsic Excitability Inmentioning
confidence: 83%
See 1 more Smart Citation
“…; Malik and Chattarji 2012;Poolos et al 2002). These experiments provide several quantitative measures of the neurons' excitability such as the rheobase and gain.…”
mentioning
confidence: 99%
“…Other conditions in which alterations of LTP are associated with altered burst responses include suppressed LTP in transgenic mouse models for Alzheimer's disease (Larson et al, 1999), suppressed LTP by diazepam (del Cerro et al, 1992), reduced LTP after neonatal lesions of contralateral hippocampus (van Praag et al, 1998), reduced LTP after inhibition of matrix metalloproteinases (Meighan et al, 2007), enhanced LTP in mice overexpressing brain protease nexin-1 (Luthi et al, 1997), facilitated LTP by an M1 muscarinic antagonist (Boddeke et al, 1992), and enhanced LTP after environmental enrichment (Malik and Chattarji, 2012), among others. Recording and analyzing the burst response pattern can help to provide a first-pass evaluation of whether an experimental manipulation affects events before or after the NMDA receptor-mediated influx of calcium that serves as the essential trigger for LTP induction.…”
Section: Theta-burst Responses As Diagnosticsmentioning
confidence: 99%